Problem Solving Ability of The Fourth Grade Students in Problem Based Learning On Two Dimensional Figures (Universitas Negeri Semarang, 2019)
This study has the purpose of testing the effectiveness of the Problem Based Learning (PBL) model on the problem-solving ability of two-dimensional figures. This study applied experimental research with a pre-test – post-test control design model. The population of this study was all of the fourth-grade students of SDN in Batangpretepurposive sampling. The sample of this study was the fourth-grade students of SDN Karangtengah 01 and the fourth-grade students of SDN Kemiri 06. The instrument of data collection used was an essay test. The analysis technique used for analyzing the data was a statistical test of paired sample t-test. The results of this study indicated that the PBL model has effectively improved the students' problem-solving abilities. This is indicated by (1) The classical completeness of problem solving abilities of students in the experimental class using PBL models which reached up to 75%, (2) The average of problem-solving abilities of students in the experimental class with PBL models was more than the average of problem-solving ability of students in the control class using the expository learning models, sig α = 5%, with sig. (2-tailed) of 0.018 since 0.018 < 0.05. therefore, the result is significant, (3) the results of the increase in problem solving ability of the experimental class students using PBL models was indicated by the result of pre-test with the percentage of learning completeness of 51%. whereas, the rest of 49% students did not complete the achievement, then the result of post-test with the result of learning completeness at 80% and the rest of 20% students did not complete, sig α = 5%, with sig. (2-tailed) obtained a score of 0.000 < 0.05. Therefore, it can be concluded that the PBL model is effective on problem-solving abilities of students in the fourth-grade elementary school at two dimension figures material.